Integrasi Thinking Routines dalam Meningkatkan Kemampuan Berpikir Tingkat Tinggi Siswa SD - Oji Sahwono (Journal of Elementary Education Research, 2025)
This article explores the integration of Thinking Routines as an instructional approach to enhance higher-order thinking skills (HOTS) among elementary school students. Grounded in a descriptive qualitative methodology with a literature review approach, the study examines academic articles, books, and conference papers accessed through databases such as Google Scholar. Data were analyzed using thematic content analysis to identify recurring concepts, implementation strategies, and findings related to Thinking Routines in deep learning.The findings indicate that Thinking Routines—such as See-Think-Wonder, Think-Pair-Share, Claim-Support-Question, and Compass Points—support deep learning by encouraging observation, reasoning, metacognition, and reflective dialogue. These routines help students understand concepts more deeply, make connections across learning contexts, and articulate their reasoning clearly. The approach positively influences students’ cognitive engagement, collaborative skills, and self-regulated learning. Overall, the study concludes that Thinking Routines serve as a bridge between knowledge acquisition and practical communication of ideas, preparing students to navigate real-world problem-solving situations effectively. They provide a powerful framework to cultivate deep thinking, enhance classroom discourse, and support the goals of the Merdeka Belajar curriculum in fostering independent, reflective, and critical learners.